Medical evaluation of child sexual abuse : a practical guide - Finkel, Martin; Giardino, Angelo P. (American Academy of Pediatrics, 2019)
The fourth edition of this best-selling reference is a valuable resource to clinicians and child advocates serving children and families affected by suspicions of child sexual abuse.